Pengaruh Perbandingan Sosial terhadap Welas Diri pada Remaja Akhir yang Menjalani Gap Year - Putri, Metha Hilmiyana; Istiqomah, Nur (Universitas Trunojoyo Madura, 2024)
The gap year is uncommon in Indonesia, furthermore late adolescents are often perceived as having a low level of self-compassion and tend to compare themselves with others. Therefore, the purpose of this study is to determine the effect of social comparison on self-compassion in late adolescents undergoing a gap year. The research employed a quantitative method involving 349 late adolescents and utilized a non-probability sampling technique known as purposive sampling. This study utilized two research instruments: The Self-Comparison Scale, consisting of 25 items, and the Social Comparison Scale, consisting of 19 items. The results of the hypothesis test demonstrated that the F value was 136.421, with a p-value of 0.000 (p smaller than 0.05). The R square value was 0.282, and the standardized coefficient (β) was -0.531. As a result, the hypothesis was accepted, indicating that there is indeed an effect of social comparison on self-compassion in late adolescents undergoing a gap year. The contribution of social comparison to self-compassion was found to be 28.2%. The negative value of the standardization coefficient (β) suggests a negative correlation between social comparison and self-compassion. In simpler terms, lower levels of social comparison correspond to a higher level of self-compassion in individuals, and vice versa.